Dietary Patterns in Prostate Cancer Prevention and Management : A Systematic Review of Prospective Cohort Studies and Randomized Clinical Trials - Lin, Pao Hwa; Burwell, Alanna D.; Giovannucci, Edward L.; Loeb, Stacy; Chan, June M.; Tuttle, Brandi; Nunzio, Cosimo De; Bjartell, Anders; Aronson, William; Freedland, Stephen J. (European Urology, 2025)
Background and objective: Prostate cancer (PC) is the second most common cancer and a leading cause of death among males. In this systematic review we evaluated cohort studies and randomized controlled trials (RCTs) on the relationship between dietary patterns and PC risk, progression, mortality, and biomarkers. Methods: A systematic search of MEDLINE, Embase, and Cochrane Central was conducted through June 2024 according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A total of 63 studies (49 cohort studies, 14 RCTs reports) examining dietary patterns and PC outcomes were included. Study quality was assessed using Critical Appraisal Skills Programme checklists. Key findings and limitations: Among males without PC at baseline, plant-based and healthy dietary patterns (eg, higher Healthy Eating Index, lower dietary inflammatory and hyperinsulinemic scores) were generally associated with lower total PC risk. Among patients with PC, Mediterranean, plant-based, and low-inflammatory diets were more consistently linked to lower risk of progression and PC-specific mortality. RCTs testing various diet patterns showed mixed effects on prostate-specific antigen or tumor markers. Limitations include variations in diet definitions, outcomes, and follow-up duration, and residual confounding. Conclusions and clinical implications: Healthy dietary patterns that support cardiometabolic health may also benefit PC prevention and management. While evidence appears stronger for diet in slowing PC progression after diagnosis, the impact of diet on reducing the risk of other PC outcomes should not be overlooked (eg, risk of developing PC or risk of PC death). Integrated strategies are needed to promote healthy eating, particularly for patients at risk of PC progression, as this population often has higher risk of cardiovascular disease and metabolic disorders such as diabetes.
Keywords: Cancer prevention; Cancer progression; Dietary pattern; Prospective studies; Prostate cancer; Randomized controlled trial